UPAYA PENGEMBANGAN PRESTASI OLAHRAGA BOLA VOLI MELALUI METODE CERAMAH PLUS SISWA KELAS VII SMKN 4 RAMBAH TAHUN PELAJARAN 2018/ 2019 - Satria Daulay (STKIP ROKANIA, 2019)
The purpose of this study was (a) to describe an increase in increase in physical education learning achievement in students after the lecture method was applied plus (b) to know the motivation for learning physical education after the application of the lecture method plus. This research uses action research with two rounds. Each round consists of two stages, namely: design, activity and observation, refining and revision. The target of this study was the tenth grade students of SMK Negeri 4 Rambah from the data obtained in the form of test results, practices and observation sheets. From the results of the analysis, it was found that students' learning achievements in the first cycle of volleyball learning skills were completed 23.07% and the second cycle was completed 57.93% and the third cycle was 100% complete for the psychomotor domain, the first cycle for the attitude domain was complete and none students who get a C score. The conclusion of this study is the lecture method plus can have a positive effect on learning motivation of Class X students of SMK Negeri 4 Rambah and the learning model can be used as an alternative to physical education.